2022
DOI: 10.7150/jca.63490
|View full text |Cite
|
Sign up to set email alerts
|

Non-absorbable antibiotic treatment inhibits colorectal cancer liver metastasis by modulating deoxycholic acid metabolism by intestinal microbes

Abstract: Emerging evidence suggests that intestinal microbes influence the occurrence and development of colorectal cancer (CRC). However, few studies have examined the relationship between gut bacteria and liver metastasis of CRC. In this study, we found that administration of non-absorbable antibiotics inhibited liver metastasis of CRC in a mouse model compared with a control group. To elucidate the underlying mechanism, immune cell infiltration analysis, 16S rRNA sequencing, and metabolomics were performed. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Seogsong Jeong 1,2, † Sun Jae Park 1, † Minseo Kim 1,3 Young Jun Park 4 Seulggie Choi 5 Jooyoung Chang 1 Ji Soo Kim 6 Yun Hwan Oh 7 Ahryoung Ko 8 Sang Min Park 1,8…”
Section: O N S E N T T O P U B L I C At I O N Not Applicablementioning
confidence: 99%
See 1 more Smart Citation
“…Seogsong Jeong 1,2, † Sun Jae Park 1, † Minseo Kim 1,3 Young Jun Park 4 Seulggie Choi 5 Jooyoung Chang 1 Ji Soo Kim 6 Yun Hwan Oh 7 Ahryoung Ko 8 Sang Min Park 1,8…”
Section: O N S E N T T O P U B L I C At I O N Not Applicablementioning
confidence: 99%
“…Since antibiotics may disrupt intestinal dysbiosis, which has been found to affect antitumor immune surveillance and contribute to the progression of liver disease toward cancer, antibiotics may be considered an unfavorable condition regarding the risk of HCC[ 7 ]. However, interestingly, gentamicin and amikacin antibiotics have been identified to decrease the deoxycholic acid concentration in liver tissues in a mouse model[ 8 ]. Deoxycholic acid, part of the enterohepatic circulation, has been shown to induce senescence‐associated secretory phenotype in hepatic stellate cells, leading to the secretion of tumor‐promoting and inflammatory factors in the liver and facilitating the development of HCC in mice[ 9 ].…”
mentioning
confidence: 99%
“…Besides lumen cavities, various evidence proved the existence of microbiomes inside tumor tissue in a broad spectrum of tumors including breast, lung, pancreas, colon, and bone. These microbiomes disrupt immune surveillance through mediation of tumor immune escape and activation of immunosuppressive pathways in the tumor microenvironment (TME). Tan et al . found that Porphyromonas gingivalis inside pancreatic cancer drove neutrophils to shape the immune microenvironment by neutrophil extracellular trap (NET) formation …”
mentioning
confidence: 99%